2010
DOI: 10.1111/j.1476-5381.2010.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of transient receptor potential melastatin channels in the vasculature

Abstract: Mammalian transient receptor potential melastatin (TRPM) non-selective cation channels, the largest TRP subfamily, are widely expressed in excitable and non-excitable cells where they perform diverse functions ranging from detection of cold, taste, osmolarity, redox state and pH to control of Mg 2+ homeostasis and cell proliferation or death. Recently, TRPM gene expression has been identified in vascular smooth muscles with dominance of the TRPM8 channel. There has been in parallel considerable progress in dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 131 publications
4
28
0
Order By: Relevance
“…In situ menthol produced Ca 2+ transients that consisted of an initial phasic component, followed by a sustained component. 28, 29 Johnson et al 8 demonstrated that TRPM8 channel activation in the rat artery causes vasoconstriction or vasodilation depending on previous vasomotor tone. However, our results suggest that menthol ultimately reduced the vascular reactivity by inhibiting calcium signaling-mediated RhoA/ROCK pathway inhibition based on of the following reasons: (1) arteries pretreated with menthol showed significant lower reactivity to vasoconstrictors; (2) in the absence of extracellular calcium, agonists only caused weak vasoconstriction, but adding calcium evoked significant vasoconstriction, which was dose dependently inhibited by menthol, indicating that menthol inhibited Ca 2+ influx; (3) the tonic contraction that represents SR Ca 2+ release-mediated RhoA/ROCK activation can be inhibited by menthol; (4) in TRPM8 −/− mice, menthol failed to inhibit U46619-induced vasocontraction and the related vascular calcium signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In situ menthol produced Ca 2+ transients that consisted of an initial phasic component, followed by a sustained component. 28, 29 Johnson et al 8 demonstrated that TRPM8 channel activation in the rat artery causes vasoconstriction or vasodilation depending on previous vasomotor tone. However, our results suggest that menthol ultimately reduced the vascular reactivity by inhibiting calcium signaling-mediated RhoA/ROCK pathway inhibition based on of the following reasons: (1) arteries pretreated with menthol showed significant lower reactivity to vasoconstrictors; (2) in the absence of extracellular calcium, agonists only caused weak vasoconstriction, but adding calcium evoked significant vasoconstriction, which was dose dependently inhibited by menthol, indicating that menthol inhibited Ca 2+ influx; (3) the tonic contraction that represents SR Ca 2+ release-mediated RhoA/ROCK activation can be inhibited by menthol; (4) in TRPM8 −/− mice, menthol failed to inhibit U46619-induced vasocontraction and the related vascular calcium signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing cerebellum, PregS strongly and reversibly enhances glutamate release onto Purkinje cells (PCs) of neonatal rats, an effect that is independent of several PregS‐sensitive targets; namely, NMDA, glycine, α7 nicotinic acetylcholine, and σ1 receptors, as well as voltage‐gated Ca 2+ channels (Zamudio‐Bulcock and Valenzuela 2011). PregS increases glutamate release by enhancing Ca 2+ entrance into pre‐synaptic terminals via a target that is sensitive to La 3+ , a non‐selective agent that modulates a number of TRP channel subtypes and is known to block TRPM3 (Zholos 2010; Zamudio‐Bulcock and Valenzuela 2011). Based on this finding, we hypothesized that TRPM3 channels are expressed at developing glutamatergic synapses on PCs and that they mediate the PregS‐induced enhancement of glutamatergic transmission.…”
mentioning
confidence: 99%
“…The TRPM subfamily includes 8 subgroups (TRPM1, TRPM2, TRPM3, TRPM4, TRPM5, TRPM6, TRPM7 and TRPM8), which are considered to have roles in tumorigenesis, cell proliferation and differentiation (11,14). The TRPM subfamily takes its name from the melastatin protein, which is defined as potential tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%